Determinants of exercise adherence and contamination in a randomized controlled trial in cancer patients during and after allogeneic HCT - Kühl, Rea; Schmidt, Martina; Dreger, Peter; Steindorf, Karen; Bohus, Martin; Wiskemann, Joachim (Supportive care in cancer, 2016)
BackgroundEvidence from randomized controlled trials is growing that exercise interventions are beneficial in cancer patients receiving allogeneic stem cell transplantation (allo-HCT). However, information about adherence to exercise interventions and exercise contamination in control groups is lacking. This information is crucial for the interpretation of study results. We therefore examined the determinants of exercise adherence and contamination in different treatment periods during (inpatient) and after (outpatient) allo-HCT.MethodsOne hundred fifty-three patients scheduled for allo-HCT were randomized to a 1-year partly supervised exercise intervention (endurance and resistance exercise) or to a control group. Adherence was assessed via exercise logs and contamination via questionnaires.ResultsAdherence varied between 66 % (inpatient) and 78 % (outpatient) in different treatment periods. During (inpatient) transplantation period, higher adherence was significantly associated with lower fatigue (P = 0.004) and with having children at home (P = 0.049). Adherence after discharge was positively associated with endurance performance (P = 0.003); higher adherence after day 100 was associated with exercise activity prior allo-HCT (P = 0.010) and higher adherence after discharge (P = 0.001). Contamination among controls was high with 54 % and significantly associated with muscle strength (P = 0.025) and fatigue (P = 0.050).ConclusionExercise adherence in different treatment periods was determined by different variables, and contamination among controls was evident. These findings may have important implications for correct interpretation of randomized exercise intervention trials.